A minimum size of the search cube in the MAFA-ILS method - Nowel, Krzysztof; Cellmer, Sławomir; Kwasniak, Dawid (International Conference “Environmental Engineering”, 2017)
The Modified Ambiguity Function Approach – Integer Least Squares (MAFA-ILS) is one of the modern method for the precise real-time GNSS positioning, for many applications such as geodesy or surveying engineering. Contrary to the classic approach, in the MAFA-ILS method the solution is sought in the coordinate domain. However, to obtain a proper solution, the search region cannot be too small. On the other hand, to have an effective solution – in the computational load sense – this region cannot be too big. In this case the determination of the minimum size of appropriate search region is not a trivial task. The paper presents a certain solution of this problem.